Shadow imaging for panoptical visualization of brain tissue in vivo - Yulia Dembitskaya; Andrew K. J. Boyce; Agata Idziak; Atefeh Pourkhalili Langeroudi; Misa Arizono; Jordan Girard; Guillaume Le Bourdellès; Mathieu Ducros; Marie Sato-Fitoussi; Amaia Ochoa de Amezaga; Kristell Oizel; Stephane Bancelin; et al. (Nature Communications)
Abstract Progress in neuroscience research hinges on technical advances in visualizing living brain tissue with high fidelity and facility. Current neuroanatomical imaging approaches either require tissue fixation (electron microscopy), do not have cellular resolution (magnetic resonance imaging) or only give a fragmented view (fluorescence microscopy). Here, we show how regular light microscopy together with fluorescence labeling of the interstitial fluid in the extracellular space provide comprehensive optical access in real-time to the anatomical complexity and dynamics of living brain tissue at submicron scale. Using several common fluorescence microscopy modalities (confocal, light-sheet and 2-photon microscopy) in mouse organotypic and acute brain slices and the intact mouse brain in vivo, we demonstrate the value of this straightforward ‘shadow imaging’ approach by revealing neurons, microglia, tumor cells and blood capillaries together with their complete anatomical tissue contexts. In addition, we provide quantifications of perivascular spaces and the volume fraction of the extracellular space of brain tissue in vivo.